PENERAPAN MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN BIOLOGI: LITERATURE REVIEW - Ganda Doloksaribu, David; Ariza, Cynthia; Putri; Lestari, Farina; Siburian, Jodion; Sadikin, Ali; Mardiyanti, Lely (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of the Discovery Learning model on students’ critical thinking skills through a literature review method. The study was conducted by collecting and analyzing 20 scientific articles related to the implementation of Discovery Learning in various levels of education, including elementary school, junior high school, senior high school, and higher education. The data sources were obtained from national journals, proceedings, and scientific articles indexed through Google Scholar and several educational journal databases. The stages of the study included identifying research topics, searching relevant articles, selecting articles based on suitability, analyzing research findings, and drawing conclusions from the reviewed literature. The results of the review indicate that the Discovery Learning model has a positive and significant effect on improving students’ critical thinking skills. This learning model encourages students to actively participate in discovering concepts, analyzing problems, and solving problems independently. In addition, Discovery Learning also improves learning motivation, learning outcomes, student activity, and conceptual understanding. The use of supporting learning media such as multimedia, interactive CDs, smart stickers, and digital platforms also increases the effectiveness of Discovery Learning implementation. Therefore, the Discovery Learning model can be used as an alternative learning model to support the development of 21st century skills, especially critical thinking skills.